The Emotional Museum. Thoughts on the “Secular Relics” of Nineteenth-Century History Museums in Paris and their Posterity - Felicity Bodenstein (Conserveries Mémorielles)
This article examines the discourse elaborated in Paris’ historical museums during the nineteenth century through the display of personal, private objects “having belonged to” famous historical figures, artistes and writers. How and why do we exhibit objects in and of themselves as banal as the handkerchief of Napoleon or locks of Marie-Antoinette’s hair? In the scheme of the rational public museum, what meaning was and is still given to these objects of little documentary or artistic importance?Indeed this museographical tradition still holds an important place in museums today, especially in biographical or personal museums, its appearance during the Revolution and its subsequent development will be considered as the transposition of a commemorative practice taken from Catholicism and introduced into the secular world of French Republican museum but also as a transfer from the private to the public sphere. This allow us to examine the agency of such objects as triggers that allow history to be experienced as an emotion.